2021
DOI: 10.1021/acs.joc.0c01948
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Catalyzed [3 + 2] Annulation of Morita–Baylis–Hillman Carbonates with Isoxazole-Based Alkenes

Abstract: A phosphine-catalyzed [3 + 2] annulation of Morita–Baylis–Hillman (MBH) carbonates with 3-methyl-4-nitro-5-styrylisoxazoles has been developed to afford various multifunctional isoxazoles in moderate to good yields with moderate to excellent diastereoselectivities. With a spirocyclic chiral phosphine as the catalyst, up to 89% ee was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In particular, Lu et al reported the first [3 + 2]-annulation of MBH carbonates with the aid of phosphane . Subsequently, organocatalytic asymmetric [3 + 2]-annulation of MBH carbonates garnered particular attention. Independently, Chen’s group has gracefully developed new MBH carbonates from isatins, which were successfully involved in organocatalytic stereoselective [3 + 2]-annulations. Notably, the organocatalytic stereoselective annulation of MBH carbonates has offered a key platform for the construction of functionalized enantioenriched carbo- and heterocycles . Although great progress has been achieved in this field, the core framework of MBH carbonates is monotonous and limited to the classical MBH adducts from aldehyde (Scheme A) and isatins (Scheme B).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Lu et al reported the first [3 + 2]-annulation of MBH carbonates with the aid of phosphane . Subsequently, organocatalytic asymmetric [3 + 2]-annulation of MBH carbonates garnered particular attention. Independently, Chen’s group has gracefully developed new MBH carbonates from isatins, which were successfully involved in organocatalytic stereoselective [3 + 2]-annulations. Notably, the organocatalytic stereoselective annulation of MBH carbonates has offered a key platform for the construction of functionalized enantioenriched carbo- and heterocycles . Although great progress has been achieved in this field, the core framework of MBH carbonates is monotonous and limited to the classical MBH adducts from aldehyde (Scheme A) and isatins (Scheme B).…”
Section: Introductionmentioning
confidence: 99%
“…Cycloaddition reactions are one of the most frequented classes of reactions in organic chemistry. In synthetic chemistry, isatin has a highly reactive C-3 carbonyl group and complex multi-spiro-heterocycles can be constructed by implying 1,3-dipolar cycloaddition reactions ( Borad et al, 2014 ; Zhu et al, 2017 ; Dwivedi et al, 2021 ), Morita–Baylis–Hillman reaction ( Deng et al, 2011 ; Liao et al, 2021 ), electrocyclization ( Viswambharan et al, 2010 ), and photo-induced reactions ( Wang et al, 2005 ). The 1,3-dipolar cycloaddition reactions (1,3-DCR) are a fascinating set of protocols that are often regarded as the most competent process and opens new vistas in the field of furnishing efficient and high-yield products in a regio- and stereo-controlled fashion ( Coldham and Hufton, 2005 ; Ramesh et al, 2018 ; Reddy et al, 2018a ; Reddy et al, 2018b ; Kumar et al, 2019 ; ).…”
Section: Introductionmentioning
confidence: 99%
“…As one type of the most successful phosphine acceptors, typical aromatic aldehyde or formaldehyde-derived MBH carbonates showed their strong and diverse reactivity to present as a reliable building block in phosphine-catalyzed annulations . The highly reactive zwitterionic intermediate generated from MBH carbonates underwent (3 + 2), (3 + 3), (3 + 4), (3 + 6), (1 + 4), and cascade annulations with electrophiles or nucleophiles (Scheme a). However, all of those reactions depended on the reactivity involving the α, β, and β′-carbon of the aromatic aldehyde or formaldehyde-derived MBH carbonates, and remote (more than 3 bonds of distance from the phosphine center) activation and functionalization still remain challenging.…”
mentioning
confidence: 99%